Tokoh Politik Islam Era Orde Lama Indonesia: Kajian Pemikiran KH Idham Chalid Dalam Menerima Konsep Demokrasi Terpimpin Tahun 1965 - Andri Nurjaman; Arzam Arzam; Zufriani Zufriani; Doli Witro (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2022)
After the ups and downs of the cabinet during the parliamentary democracy or often referred to as liberal democracy, Soekarno implemented a new concept and model of democracy since 1959 called guided democracy. Nahdlatul Ulama which at that time was chaired by KH Idham Chalid accepted Soekarno’s guided democracy concept, and NU was the only Islamic party that accepted guided democracy. The purpose of writing this article is to find out the political thoughts of KH Idham Chalid in accepting the concept of guided democracy. The method used in the preparation of this article uses the historical method, namely heuristics (search for sources), the main primary sources are the Islamic fire magazine published in 1965 and the book Islam and Guided Democracy, both primary sources written directly by KH Idham Chalid. Criticism (source selection), interpretation (interpretation) and historiography (writing). The results of this study are known that KH Idham Chalid accepted the concept of guided democracy because NU’s politics were flexible and chose to cooperate with the authorities, he had the idea that the concept of guided democracy was in accordance with Islamic teachings, namely syuro or deliberation.